Case report: Dissolving carotid plaque associated to Lorlatinib-related dyslipidemia - Mayer-Suess, Lukas; Knoflach, Michael; Pircher, Andreas; Kiechl, Stefan; Schmidauer, Christoph; Hametner, Eva (Frontiers in Oncology, 2024)
We present a case with prolonged Lorlatinib-related dyslipidemia causing internal carotid artery stenosis, putting the patient at risk of cerebrovascular events. Through intensified lipid-lowering treatment and dose reduction of Lorlatinib, LDL-C levels decreased markedly. Surprisingly, the left sided internal carotid artery stenosis dissolved accordingly. Due to the high efficacy of the new selective tyrosine kinase inhibitors and resulting long-term treatment, it is essential to carefully follow-up and include drug specific side effect monitoring. This case emphasizes that Loraltinib-related dyslipidemia has to be taken seriously and treatment should be initiated as promptly as possible. We conclude that in cases were lipid dysregulation remains and Lorlatinib treatment has to be continued, cerebrovascular appraisal through ultrasound should be considered and, if stenosis is evident, intensified treatment regimen of dyslipidemia or dose reduction of Lorlatinib should be discussed in an interdisciplinary setting.